Martial arts: mindful exercise to combat stress - Wesley Naves-Bittencourt; Arilson Mendonça-; Matthew Stults-Kolehmainen; Eduardo Fontes; Cláudio Córdova; Marcelo Demarzo; Daniel Boullosa (Asociación Española de Ciencias del Deporte, 2015)
Stress can promote cardiovascular and metabolic responses that may favor the development of a number of diseases, especially when it is experienced chronically. Mindfulness (MF) practices are adaptations from eastern meditative techniques which are utilized in different psycho-social therapies for promotion of physical and mental health. The psychological construct of MF refers to a special form of attention to internal and external phenomena in the present moment, including openness to experience in a non-critical attitude (i.e. without judgments). Mindfulness-based practices and interventions are particularly effective in promoting health for clinical conditions involving chronic stress, anxiety and depressive symptoms. Similarly, regular exercise has multifarious benefits for health, especially activities that strongly integrate both psychological and physiological training. Such is the case for martial arts (MA), the whole of which could be classified as mindful movements. Given that MA requires expenditure of energy done with a high level of concentration, engagement in this form of exercise may provide an interesting and novel strategy for enhancing physical and mental benefits. The regular practice of MA could elevate MF levels of practitioners and thus influence positively on stress management and therefore quality of life and well-being.